Program Tahfidzul Qur’an dalam Meningkatan Mutu Pembelajaran al Qur’an Hadits - Mufidah, Izzatul (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
The implementation of education by both the government and foundations will be in the spotlight for the community, especially with regard to the quality or not of the processes and services carried out by a school or madrasa. In order to realize quality education that is relevant to the needs of society that is competitive in global life, it is deemed necessary to optimize the entire potential of the institution, both human resources, material resources, quality of learning, and quality of graduates. In this case, MI Al-Ittihad established a superior program as an effort to improve the quality of learning in school. The program is Tahfidzul Quran. Based on this background, the researchers asked the following research questions (1) How is the implementation of the Tahfidzul Qur'an program in improving the Quality of Al-Quran Hadith Learning at MI Al-Ittihad Tanjungkalang Ngronggot Nganjuk for the 2020/2021 academic year? (2) The impact of the tahfidz program on the quality of learning the Al-Quran Hadith at MI Al-Ittihad for the 2020-2021 Academic Year?